AIAA SCITECH 2022 Forum 2022
DOI: 10.2514/6.2022-1341
|View full text |Cite|
|
Sign up to set email alerts
|

Sloshing Wing Dynamics - 2nd Year Project Overview

Abstract: The SLOshing Wing Dynamics (SLOWD) project aims to investigate the modelling of fuel sloshing physics to reduce the design loads on aircraft structures. This goal will be achieved through investigating the damping effect of sloshing on the dynamics of flexible wing-like structures carrying liquid (fuel) via the development of experimental set-ups complemented by novel numerical and analytical tools. The primary focus of the project is the application of modelling capabilities to the wing design of large civil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In this context, the European SLOshing Wing Dynamics (SLOWD) research project [1,2] investigates how the fuel slosh affects the damping of the civil aircraft wings oscillations. One of the main objectives of the SLOWD project is to tackle the vertical and violent sloshing problem using different methodologies, namely, experimental [3][4][5], numerical [6][7][8][9][10][11] and based on Reduced Order Models (ROMs) [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the European SLOshing Wing Dynamics (SLOWD) research project [1,2] investigates how the fuel slosh affects the damping of the civil aircraft wings oscillations. One of the main objectives of the SLOWD project is to tackle the vertical and violent sloshing problem using different methodologies, namely, experimental [3][4][5], numerical [6][7][8][9][10][11] and based on Reduced Order Models (ROMs) [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…We focus our work on the analysis of a set of physical experiments carried out at the Airbus Protospace facilities in Filton (UK) in August 2018. The campaign demonstrated that liquid sloshing affects the dynamics of a free-vibrating cantilever beam, leading to a substantive increase in its damping characteristics (Gambioli et al, 2019;Titurus et al, 2019). These preliminary findings formed the basis for the SLOshing Wing Dynamics (SLOWD) H2020 project, which aims to exploit the potential of fuel sloshing as a mean for aircraft loads alleviation (Gambioli et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a reliable prediction of the sloshing dynamics is essential for the design and operation of the system subjected to sloshing influence. This work forms part of the wider EU Horizon 2020 SLOWD (SLOshing Wing Dynamics) project and investigates the physics of fuel sloshing in the context of wing-like structures in order to build reliable experimental, numerical and theoretical modelling frameworks that inform future wing designs and reduce design conservatism [10,11].…”
Section: Introductionmentioning
confidence: 99%